2021
DOI: 10.1021/acs.langmuir.1c00146
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Well-Exfoliated Poly(ethylene-co-vinyl acetate)/α-Zirconium Phosphate Nanocomposites

Abstract: Poly(ethylene-co-vinyl acetate) (PEVAc) nanocomposites containing exfoliated α-zirconium phosphate (ZrP) have been prepared using a simple solution mixing method to improve their barrier and mechanical properties. ZrP was pre-exfoliated with a surfactant, followed by additional targeted surface functionalization and surfactant exchange to allow for hydrogen bonding of ZrP with the acetate functionality on PEVAc and to improve ZrP surface hydrophobicity. The solvent is found to play an important role in stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…According to previous studies, the researchers prepared stripped ZrP with surfactant and also found no ZrP peaks in their XRD patterns. 30 , 31 Due to the exfoliation effect, ZrP was likely to transform into an amorphous state, which led to the disappearance of the ZrP characteristic peaks. Similarly, in this study, the existence of Pluronic L64 in the calcination process might affect the crystallization of ZrP, possibly causing the absence of ZrP characteristic peaks in the XRD and GIXRD results.…”
Section: Resultsmentioning
confidence: 99%
“…According to previous studies, the researchers prepared stripped ZrP with surfactant and also found no ZrP peaks in their XRD patterns. 30 , 31 Due to the exfoliation effect, ZrP was likely to transform into an amorphous state, which led to the disappearance of the ZrP characteristic peaks. Similarly, in this study, the existence of Pluronic L64 in the calcination process might affect the crystallization of ZrP, possibly causing the absence of ZrP characteristic peaks in the XRD and GIXRD results.…”
Section: Resultsmentioning
confidence: 99%
“…The "tortuous pathway" strategy has largely been adopted to impart barrier properties of the assembled hybrids containing inorganic nanosheets, which are generally considered impermeable for guest molecules. [53,[85][86][120][121][122][123][124][125][126] α-ZrP is a particularly ideal candidate because it can be completely exfoliated into single-layer nanosheets and the aspect ratio of the nanosheets can be well-controlled by synthesizing layered α-ZrP crystals with various lateral dimensions as discussed above. When single-layer α-ZrP nanosheets are well dispersed, their concentration, aspect ratio, curvature, and orientation dictate the barrier properties of the assembled hybrids.…”
Section: Barrier Propertiesmentioning
confidence: 99%
“…Combining metal–organic frameworks with polymers enhances their processibility. The influence of the polymer network on the viscoelastic properties of polymer nanocomposites has been examined extensively. , …”
Section: Introductionmentioning
confidence: 99%